The effects of productivity and benefits on unemployment: Breaking the link - Alessio J. G. Brown; Britta Kohlbrecher; Christian Merkl; Dennis J. Snower (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
In the standard macroeconomic search and matching model of the labor market, there is a tight link between the quantitative effects of (i) aggregate productivity shocks on unemployment and (ii) unemployment benefits on unemployment. This tight link is at odds with the empirical literature. We show that a two-sided model of labor market search where the household and firm decisions are decomposed into job offers, job acceptances, firing, and quits can break this link. In such a model, unemployment benefits affect households' behavior directly, without having to run via the bargained wage. A calibration of the model based on U.S. JOLTS data generates both a solid amplification of productivity shocks and a moderate effect of benefits on unemployment. Our analysis shows the importance of investigating the effects of policies on the households' work incentives and the firms' employment incentives within the search process.
Keywords: E24; E32; J63; J64; 330; unemployment benefits; search and matching; aggregate shocks; macro models of the labor market